2015
DOI: 10.1093/petrology/egv038
|View full text |Cite
|
Sign up to set email alerts
|

The Early Proterozoic Matachewan Large Igneous Province: Geochemistry, Petrogenesis, and Implications for Earth Evolution

Abstract: 32 33The Matachewan Large Igneous Province (LIP) is interpreted to have formed during the early

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 154 publications
(245 reference statements)
0
20
0
2
Order By: Relevance
“…On the basis of coeval magmatism, Bleeker and Ernst (2006) suggested that the Fennoscandian Shield was situated along the southern margin of the Superior Craton at the end of the Archean. The tectonic setting as well as the mantle source of magmatism remain under debate, but most researchers prefer a rift-related mantle plume melting model followed by large-scale contamination with older felsic crustal rocks to explain the trace element and isotopic signature of the igneous rocks (Amelin et al, 1995;Barnes et al, 2001;Ciborowski et al, 2015;Hanski et al, 2001b;Puchtel et al, 1997;Yang et al, 2016).…”
Section: Geological Settingmentioning
confidence: 99%
“…On the basis of coeval magmatism, Bleeker and Ernst (2006) suggested that the Fennoscandian Shield was situated along the southern margin of the Superior Craton at the end of the Archean. The tectonic setting as well as the mantle source of magmatism remain under debate, but most researchers prefer a rift-related mantle plume melting model followed by large-scale contamination with older felsic crustal rocks to explain the trace element and isotopic signature of the igneous rocks (Amelin et al, 1995;Barnes et al, 2001;Ciborowski et al, 2015;Hanski et al, 2001b;Puchtel et al, 1997;Yang et al, 2016).…”
Section: Geological Settingmentioning
confidence: 99%
“…Geochemistry, Geophysics, Geosystems intrusions in the Superior and Wyoming Cratons, are thought to be part of one the oldest large igneous provinces on Earth (Ciborowski et al, 2015;Heaman, 1997).…”
Section: 1029/2018gc007548mentioning
confidence: 99%
“…On the basis of coeval magmatism, it was suggested that the Fennoscandian Shield was situated along the southern margin of the Superior craton at the end of the Archean [14]. The tectonic setting, as well as the mantle source of magmatism, remain under debate, but most researchers prefer a rift-related mantle plume melting model followed by large-scale contamination with older felsic crustal rocks to explain the trace element and isotopic signature of the igneous rocks [15][16][17][18][19][20].…”
Section: Geologic Settingmentioning
confidence: 99%